Design and implementation of a wireless control system applied to a 3-DoF redundant robot using Raspberry Pi interface and User Datagram Protocol. (October 2021) - Urrea, Claudio; Kern, John
Abstract: This work addresses the design and implementation of a wireless connection for the remote control of the joints of a redundant 3-DoF 1 manipulator robot. To this end, low-cost devices able to establish master/slave connections are used as closed control loops to calculate both control in the master device and actuation in the slave devices. To test the performance of this wireless connection, classic robot controllers are designed, simulated, analyzed, implemented, and compared through a decentralized structure. The platform Raspberry Pi and UDP 2 protocol are used to obtain and process data sent to the robot control system, and to send control signals to the robot actuators. Additionally, the feasibility of synthetizing control systems for highly non-linear robots and, in turn, of commanding this system through a remote wireless communication system is demonstrated.